2012
DOI: 10.1039/c2em10960c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of growth conditions on transport behavior of E. coli

Abstract: The aim of this investigation is to determine the effect that growth solution has on the cell surface properties and transport behavior of eleven Escherichia coli isolates through saturated porous media. The two growth solutions used were a standard laboratory growth medium (LB) and a dairy manure extract solution. In general, cells grown in manure extract were more hydrophobic, had a more negative zeta potential, had lower amounts of surface macromolecules, and had lower attachment efficiencies than isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…As in previous work using regression analysis, attachment efficiency was found to be correlated to electrophoretic mobility (72)(73)(74) and hydrophobicity (77). Additionally, attachment efficiency was inversely proportional to the EPS sugar-to-protein ratio (P Ͻ 0.05) (74).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As in previous work using regression analysis, attachment efficiency was found to be correlated to electrophoretic mobility (72)(73)(74) and hydrophobicity (77). Additionally, attachment efficiency was inversely proportional to the EPS sugar-to-protein ratio (P Ͻ 0.05) (74).…”
Section: Discussionsupporting
confidence: 48%
“…The extensive phenotypic cell characteristics tested-hydrophobicity, electrophoretic mobility (EPM), radius, extracellular polymeric substance (EPS) content, and attachment efficiencywere chosen because they have been linked to the fate and transport of microorganisms in the environment (42,(72)(73)(74) and can be used for comparative evaluation of different environmental microbial communities. In the absence of E. coli O157:H7, cells from the colon had lower hydrophobicity, EPM, EPS, and attachment efficiency values than microbial communities in the aquatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Within the current body of literature, little attention has been paid to the fate of waterborne pathogenic microbes under nutrient-deficient conditions that prevail in the natural environment and wastewater treatment facilities (17,(22)(23)(24). Walker reported that, for both Burkholderia cepacia G4g and ENV435g, the deposition rates for cells cultivated in nutrient-rich medium differed from those in nutrient-poor basal salt medium (17).…”
mentioning
confidence: 99%
“…Walker reported that, for both Burkholderia cepacia G4g and ENV435g, the deposition rates for cells cultivated in nutrient-rich medium differed from those in nutrient-poor basal salt medium (17). In addition, Marcus et al investigated the effect of the growth solution on the cell surface properties and transport behavior of 11 Escherichia coli isolates, and they observed significant differences in cell surface properties and transport behavior for some cells according to the growth solution (24). However, to our knowledge, no such studies have been performed on bacterial deposition and transport in aqueous chemistry relevant to treated wastewater.…”
mentioning
confidence: 99%
“…The impact on various growth conditions on the transport of E. coli was also investigated (Marcus et al, 2012). When measuring E. coli grown in a standard laboratory growth medium and a dairy manure extract solution, cells grown in manure extract were more hydrophobic, had a more negative zeta potential, had lower amounts of surface macromolecules, and had lower attachment efficiencies than cells grown in laboratory growth medium.…”
Section: Occurrence Of Fecal Indicators In Watershedsmentioning
confidence: 99%